Service Innovation as a Mediator of Organizational Factors and Customer Satisfaction: Insights from Taiwan’s Tourism Industry - Ramli Hatma; Abdul Nasir Rachman; Hardiyono Hardiyono; Siti Mujahida; Muhammad Azizurrohman (Jurnal Organisasi dan Manajemen, 2025)
Purpose – This study explores the impact of employee well-being, transformational leadership, and the work environment on service innovation and customer satisfaction in Taiwan’s tourism industry.  Methodology – A cross-sectional survey of 295 respondents, including workers and tourists, was conducted using a random sampling method and a 7-point Likert scale questionnaire. This quantitative study employs structural equation modelling (SEM) to examine how employee well-being, leadership style, and the work environment influence service innovation and customer satisfaction in Taiwan’s tourism industry. Findings – The results demonstrate that employee well-being, transformational leadership, and a supportive work environment significantly enhance service innovation, which, in turn, positively influences customer satisfaction. Service innovation also acts as a mediator in the relationship between organizational factors and customer satisfaction. Originality – The originality of this manuscript lies in its focus on the mediating role of service innovation in the relationship between employee well-being, leadership style, work environment, and customer satisfaction within the context of Taiwan’s tourism industry.